2020
DOI: 10.1111/jfpp.15143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cinnamaldehyde incorporation on the structural and physical properties, functional activity of soy protein isolate‐egg white composite edible films

Abstract: Cinnamaldehyde (CIN) was added to edible composite films of soy protein isolate (SPI) and egg white (EW) to develop active food packaging. The effects of adding 2%–10% CIN on the structural, physical, and functional properties of the SPI/EW films were systematically evaluated. Fourier‐transform infrared spectroscopy and X‐ray diffraction suggested the excellent compatibility of the components because hydrogen bonding occurred. Scanning electron microscopy indicated CIN affected the structure of the films. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…As shown in Figure 7, in comparison to sodium alginate film, the composite films had a glossy and continuous surface, without bubbles and wrinkles, it shows the great compatibility of sodium alginate and phytic acid (Zhao et al, 2020), moreover, Nisin and glycerin are evenly distributed in the film, thus forming an edible film with a good surface (El Miri et al, 2015). In Figure 6, we can also see many folds on the surface of sodium alginate, simple sodium alginate may tends to coating unevenly, for storing waxy corn kernels is a big disadvantage.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 7, in comparison to sodium alginate film, the composite films had a glossy and continuous surface, without bubbles and wrinkles, it shows the great compatibility of sodium alginate and phytic acid (Zhao et al, 2020), moreover, Nisin and glycerin are evenly distributed in the film, thus forming an edible film with a good surface (El Miri et al, 2015). In Figure 6, we can also see many folds on the surface of sodium alginate, simple sodium alginate may tends to coating unevenly, for storing waxy corn kernels is a big disadvantage.…”
Section: Resultsmentioning
confidence: 99%
“…This might be attributed to the presence of CIN in the polymer matrix. A large number of previous studies have shown that CIN had inhibitory effects on the growth of a variety of bacteria, because CIN might damage the cell membrane of bacteria, leading to changes in cytoplasmic leakage and membrane permeability [ 41 , 42 ]. Similarly, for E. coli , the number of colonies in the film containing CIN was significantly reduced by 0.65 and 0.57 Log 10 CFU/mL, respectively, compared with the control group.…”
Section: Resultsmentioning
confidence: 99%